Comorbidity between schizophrenia and keratoconus. (January 2017) - Schürhoff, Franck; Leboyer, Marion; Szöke, Andrei
Highlights: There is a comorbidity between schizophrenia and keratoconus, which are both complex disorders involving genetic and environmental susceptibility factors. Comorbidity between physical and mental illnesses may have important implications regarding the underlying biological processes that drive their pathophysiology. The co-occurrence of schizophrenia and keratoconus indicates future research directions including the role of inflammation, genetic variants at the 13q32 site and oxidative stress. This report also emphasizes the need to systematically inquire about the presence of psychotic symptoms in patients with keratoconus and ophthalmologic signs in patients with psychosis.